2021
DOI: 10.5194/nhess-21-1887-2021
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami damage to ports: cataloguing damage to create fragility functions from the 2011 Tohoku event

Abstract: Abstract. Modern tsunami events have highlighted the vulnerability of port structures to these high-impact but infrequent occurrences. However, port planning rarely includes adaptation measures to address tsunami hazards. The 2011 Tohoku tsunami presented us with an opportunity to characterise the vulnerability of port industries to tsunami impacts. Here, we provide a spatial assessment and photographic interpretation of freely available data sources. Approximately 5000 port structures were assessed for damage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Therefore, the tide level of +0.7 m is selected as the high tide level [18] in other tsunami case scenarios for hazard and risk assessment in sections 5 and 6. In a previous study [4], eight common port industries were identified in the Tohoku region based on their occupancies. The participants in this study could be classified into five of those industries as follows:…”
Section: Numerical Simulation Of Future Tsunami Scenariosmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the tide level of +0.7 m is selected as the high tide level [18] in other tsunami case scenarios for hazard and risk assessment in sections 5 and 6. In a previous study [4], eight common port industries were identified in the Tohoku region based on their occupancies. The participants in this study could be classified into five of those industries as follows:…”
Section: Numerical Simulation Of Future Tsunami Scenariosmentioning
confidence: 99%
“…Fig. 12 shows the factory damage maps when applying structural fragility functions (Damage State 2 = Operational only after repairs) [4] to all five large tsunami scenarios. Similar to the inundation maps (Figs.…”
Section: Tsunami Risk Assessment In Sendai Portmentioning
confidence: 99%
See 3 more Smart Citations